Jose Rizal - Abaya, Marilou Diaz.; GMA Network, Inc.; GMA Films (Quezon City GMA Films, 1998)
Presents the final days of Philippine national hero Jose Rizal as he looks back on the events of his life and provides commentaries on episodes in his writings.
VHS.
Screenplay, Ricardo Lee, Jun Lana, Peter Ong Lim ; produced by Butch Jimenez, Jimmy Duavit and Marilou Diaz-Abaya ; directed by Marilou Diaz-Abaya.
Cesar Montano, Jaime Fabregas.
Keywords: Rizal, Jose -- 1861-1896 -- Drama; Feature films -- Philippines; Philippines -- History -- Revolution, 1896-1898 -- Drama